Environmentally Tough and Stretchable MXene Organohydrogel with Exceptionally Enhanced Electromagnetic Interference Shielding Performances - Yu, Yuanhang; Yi, Peng; Xu, Wenbin; Sun, Xin; Deng, Gao; Liu, Xiaofang; Shui, Jianglan; Yu, Ronghai (Nano-Micro Letters, 2022)
Conductive hydrogels have potential applications in shielding electromagnetic (EM) radiation interference in deformable and wearable electronic devices, but usually suffer from poor environmental stability and stretching-induced shielding performance degradation. Although organohydrogels can improve the environmental stability of materials, their development is at the expense of reducing electrical conductivity and thus weakening EM interference shielding ability. Here, a MXene organohydrogel is prepared which is composed of MXene network for electron conduction, binary solvent channels for ion conduction, and abundant solvent-polymer-MXene interfaces for EM wave scattering. This organohydrogel possesses excellent anti-drying ability, low-temperature tolerance, stretchability, shape adaptability, adhesion and rapid self-healing ability. Two effective strategies have been proposed to solve the problems of current organohydrogel shielding materials. By reasonably controlling the MXene content and the glycerol-water ratio in the gel, MXene organohydrogel can exhibit exceptionally enhanced EM interference shielding performances compared to MXene hydrogel due to the increased physical cross-linking density of the gel. Moreover, MXene organohydrogel shows attractive stretching-enhanced interference effectiveness, caused by the connection and parallel arrangement of MXene nanosheets. This well-designed MXene organohydrogel has potential applications in shielding EM interference in deformable and wearable electronic devices. Highlights: 1 Stretchable MXene organohydrogel contains MXene network for electron conduction and water/glycerin binary solvent for ion transmission was prepared. 2 The MXene organohydrogel exhibits exceptionally enhanced EMI shielding performance compared to hydrogel, as well as low-temperature tolerance, anti-drying ability.